Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1143/jjap.49.04dh02
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Optical Power and Emission Angle of Blue Light Emitting Diodes Using Patterned Sapphire Substrates with Low Threading Dislocation Densities

Abstract: GaN blue light-emitting diodes (LEDs) with a peak emission wavelength of approximately 461 nm were fabricated on a c-face lens patterned sapphire substrate (PSS) and an unpatterened sapphire substrate (UPSS) by metal organic chemical vapor deposition (MOCVD). The crystal structure of an epitaxial GaN film was improved by using the PSS. The peak wavelengths with electroluminescence intensities of 462 and 464 nm were measured for PSS and UPSS LEDs using a 20 mA injection current. It was found that the electrolum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…In addition, a nano pattern has attracted considerable attention for the further improvement of the light extraction efficiency of InGaN-based lightemitting diodes (LEDs) as an alternative to a conventional micro pattern. [6][7][8][9][10] Nano patterns are fabricated by various methods, such as ball up of metal, 11) electron beam lithography, 12) two-beam holographic lithography, 13) NIP technique, 14) thermal lithography, 15) and a femtosecond laser technique. 16) So far, nano structures, such as a PSS, [17][18][19] a SiO 2 mask on sapphire 20) or in a GaN layer, 21) patterned p-type GaN, 22) patterned ITO, 23) and patented n-type GaN of a thin film LED, 24) have been used for the improvement in light extraction efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a nano pattern has attracted considerable attention for the further improvement of the light extraction efficiency of InGaN-based lightemitting diodes (LEDs) as an alternative to a conventional micro pattern. [6][7][8][9][10] Nano patterns are fabricated by various methods, such as ball up of metal, 11) electron beam lithography, 12) two-beam holographic lithography, 13) NIP technique, 14) thermal lithography, 15) and a femtosecond laser technique. 16) So far, nano structures, such as a PSS, [17][18][19] a SiO 2 mask on sapphire 20) or in a GaN layer, 21) patterned p-type GaN, 22) patterned ITO, 23) and patented n-type GaN of a thin film LED, 24) have been used for the improvement in light extraction efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) The use of a patterned sapphire substrate (PSS) is one means of improving LEE, and various types of PSS have been reported. [3][4][5][6][7] In a previous study, we demonstrated a high EQE using a PSS with a randomly arranged cone array. 8) In recent years, PSSs with structures such as cones and hemispheres have become popular for realizing high-efficiency LEDs, and the effect of PSSs on the LEE has been calculated by many groups.…”
mentioning
confidence: 96%